1995
DOI: 10.1207/s15327752jpa6403_9
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement Structure of the Center for Epidemiologic Studies Depression Scale

Abstract: This study examined the temporal stability of the measurement structure of the Center for Epidemiologic Studies Depression Scale (CES-D; Radloff, 1977) in 813 individuals with rheumatoid arthritis. Participants completed the CES-D (Radloff, 1977) on three occasions 1 year apart. Structural equation models and polyserial correlations were used to address methodological limitations of previous studies. Four competing measurement structures were tested with one factor, three factors, four factors, and a single se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
226
1
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(245 citation statements)
references
References 28 publications
13
226
1
1
Order By: Relevance
“…A 10% reduced risk of incidence of MI per unit increase of positive emotion scores has been demonstrated in older adults, even when controlling for negative affect (Ostir et al, 2001b). Although this study can be criticised for using a depression questionnaire to assess positive affect, previous work has demonstrated that the scale used (Center for Epidemiological Studies Á Depression scale: CES-D) subdivides into positive and negative emotion items (e.g., Miller, Markides, & Black, 1997;Sheehan, Fifield, Reisine, & Tennen, 1995). The items of the CES-D can be seen in Table 2, and four positive emotion items that load together are: 'I felt that I was just as good as other people', 'I felt hopeful about the future', 'I was happy', and 'I enjoyed life'.…”
Section: Associations With Depression and Chdmentioning
confidence: 87%
“…A 10% reduced risk of incidence of MI per unit increase of positive emotion scores has been demonstrated in older adults, even when controlling for negative affect (Ostir et al, 2001b). Although this study can be criticised for using a depression questionnaire to assess positive affect, previous work has demonstrated that the scale used (Center for Epidemiological Studies Á Depression scale: CES-D) subdivides into positive and negative emotion items (e.g., Miller, Markides, & Black, 1997;Sheehan, Fifield, Reisine, & Tennen, 1995). The items of the CES-D can be seen in Table 2, and four positive emotion items that load together are: 'I felt that I was just as good as other people', 'I felt hopeful about the future', 'I was happy', and 'I enjoyed life'.…”
Section: Associations With Depression and Chdmentioning
confidence: 87%
“…These four items load on a single PA factor (Sheehan, Fifield, Reisine, & Tennen, 1995). They include ratings of how much the participants enjoy life, the extent to which they feel hopeful about the future, their happiness, and how good they are as compared with other individuals.…”
Section: Measures Of Pamentioning
confidence: 99%
“…Scores on each individual item range from 0 -3, with higher scores indicating more frequent experience of the symptoms; the range for the summary CES-D score is 0 -60. The CES-D has been shown to exhibit adequate reliability and validity (28), including studies that have assessed its psychometric properties in patients with RA (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…Commonly used measures of depression in arthritis research include the Center for Epidemiologic Studies Depression Scale (CES-D) (11), the Geriatric Depression Scale (GDS) (12), the Hamilton Depression Inventory (HAM-D) (13), the Affect score from the Arthritis Impact Measurement Scales 2 (AIMS2-A) (14), and the Depression subscale from the Symptom Checklist-90-R (SCL-90-R) (15). Several studies have demonstrated sound psychometric properties for these scales (14 -17), including studies that have assessed their reliability and validity within the RA population (18,19), but the utility of depression measures for assessing change over time has not been as carefully examined.…”
Section: Introductionmentioning
confidence: 99%